Risk factors and transmission pathways associated with infant Campylobacter spp. prevalence and malnutrition: a formative study in rural Ethiopia - Budge, Sophie; Barnett, Megan; Hutchings, Paul; Parker, Alison; Tyrrel, Sean F.; Hassard, Francis; Garbutt, Camila; Moges, Mathewos; Woldemedhin, Fitsume; Jemal, Mohammedyasin (Public Library of Science (PLoS), 2020)
Early infection from enteropathogens is recognised as both a cause and effect of infant malnutrition. Specifically, evidence demonstrates associations between growth shortfalls and Campylobacter infection, endemic across low-income settings, with poultry a major source. Whilst improvements in water, sanitation and hygiene (WASH) should reduce pathogen transmission, interventions show inconsistent effects on infant health. This cross-sectional, formative study aimed to understand relationships between infant Campylobacter prevalence, malnutrition and associated risk factors, including domestic animal husbandry practices, in rural Ethiopia. Thirty-five households were visited in Sidama zone, Southern Nations, Nationalities and Peoples’ region. Infant and poultry faeces and domestic floor surfaces (total = 102) were analysed for presumptive Campylobacter spp. using selective culture. Infant anthropometry and diarrhoeal prevalence, WASH facilities and animal husbandry data were collected. Of the infants, 14.3% were wasted, 31.4% stunted and 31.4% had recent diarrhoea. Presumptive Campylobacter spp. was isolated from 48.6% of infant, 68.6% of poultry and 65.6% of floor surface samples. Compared to non-wasted infants, wasted infants had an increased odds ratio (OR) of 1.41 for a Campylobacter-positive stool and 1.81 for diarrhoea. Positive infant stools showed a significant relationship with wasting (p = 0.026) but not stunting. Significant risk factors for a positive stool included keeping animals inside (p = 0.027, OR 3.5), owning cattle (p = 0.018, OR 6.5) and positive poultry faeces (p<0.001, OR 1.34). Positive floor samples showed a significant correlation with positive infant (p = 0.023), and positive poultry (p = 0.013, OR 2.68) stools. Ownership of improved WASH facilities was not correlated with lower odds of positive stools. This formative study shows a high prevalence of infants positive for Campylobacter in households with free-range animals. Findings reaffirm contaminated floors as an important pathway to infant pathogen ingestion and suggest that simply upgrading household WASH facilities will not reduce infection without addressing the burden of contamination from animals, alongside adequate separation in the home.
Keywords: Animal husbandry; Malnutrition; Ethiopia; Domestic animals; Medical risk factors; Diarrhea; Poultry; Campylobacter